Pengaruh Pembelajaran Pendidikan Jasmani terhadap Hasil Belajar Siswa: (Studi Kasus SMA Muhammadiyah Bumiayu) - Galuh Henda Pramadika; Ribut Wahidi (Edukasi Elita : Jurnal Inovasi Pendidikan, 2026)
This study aims to determine the effect of Physical Education, Sports, and Health (PJOK) learning on students’ learning outcomes at SMA Muhammadiyah Bumiayu. The research method used is a quantitative method with a correlational (ex-post facto) approach. The subjects of this study were students of SMA Muhammadiyah Bumiayu selected through purposive sampling technique. The research instruments used were a closed-ended questionnaire to measure the PJOK learning implementation variable and report card documentation to measure students’ learning outcomes. Data analysis was conducted using statistical techniques to identify the relationship between variables. The results of this study are expected to provide an empirical overview of the extent to which PJOK learning contributes to improving students’ overall learning outcomes, including cognitive, affective, and psychomotor domains. Furthermore, this study is expected to serve as a reference for improving the quality of PJOK learning in schools.